Cross-cultural adaptation and validation of the First-Time Fathers Questionnaire in China. (February 2021) - Xiu-Zhen, Zhang; Jing, Zhang; Lin, Zhou; Premberg, Aasa; Dong-Mei, Ma; Meng-Yan, Xu; Guo-He, Feng; Ping, Wu; Zhao-Lan, Bao
Highlights: This study cross-culturally adapted and validated the First-Time Fathers Questionnaire (FTFQ) in the cultural context of China. It provides a validated instrument for assessing Chinese first-time fathers' experience of childbirth. It will contribute to the knowledge of first-time fathers' experience of childbirth and facilitate further actions to improve paternal satisfaction and behaviour as labour companions. Abstract: Objective: The study aimed to cross-culturally adapt and validate the First-Time Fathers Questionnaire (FTFQ) in the cultural context of China. Design: Prospective validation study. Setting: The study was conducted in four public hospitals in Hangzhou, a southeast coastal city of China. Participants: Four hundred and nineteen first-time fathers (mean age=30.45 years, SD=3.44, range 22-46) whose partners had given birth between July 20 and October 10, 2019. Methods: The instrument "First Time Fathers Questionnaire (FTFQ)" was translated and culturally adapted to the Chinese context according to the methodological criteria of the International Society for Pharmacoeconomic and Outcomes Research. The construct-related validity of the instrument was tested through EFA and CFA. Content validity was evaluated with an analysis of the expert judgment. Reliability was assessed based on the internal consistency. Results: Four domains were identified: "Worry", "Information", "Emotional Support", and "Acceptance", with 19 items and adequate internal reliability (0.86, 0.80, 0.86, and 0.72, respectively) and a total variance of 64.65%. The CFA model showed there is a good fit for the data: X 2 /df =1.20; RMSA = 0.03; CFI = 0.99; and NFI = 0.93. Additionally, each item achieved an I-CVI ≧0.83, and the S-CVI/Ave = 0.90. Key Conclusions: The Chinese version of the FTFQ is a valid and reliable instrument to assess first-time fathers' experience of childbirth in China. Implications for Practice: This study provides a validated questionnaire that is suitable for the Chinese cultural context. It contributes to the knowledge of first-time fathers' experience of childbirth and facilitate further actions to improve paternal satisfaction and behavior as labour companion.